2004
DOI: 10.1002/prot.20072
|View full text |Cite
|
Sign up to set email alerts
|

Topological thermal instability and length of proteins

Abstract: We present an analysis of the effects of global topology on the structural stability of folded proteins in thermal equilibrium with a heat bath. For a large class of single domain proteins, we computed the harmonic spectrum within the Gaussian Network Model (GNM) and determined their spectral dimension, a parameter describing the low frequency behavior of the density of modes. We found a surprisingly strong correlation between the spectral dimension and the number of amino acids in the protein. Considering tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 37 publications
(63 reference statements)
5
71
0
Order By: Relevance
“…Recently there has been an accumulation of evidence supporting the hypothesis that proteins are fractal-like objects (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The fractal nature of proteins manifests itself in the way proteins vibrate and in the manner in which they fill space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently there has been an accumulation of evidence supporting the hypothesis that proteins are fractal-like objects (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The fractal nature of proteins manifests itself in the way proteins vibrate and in the manner in which they fill space.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on proteins have already shown that gðωÞ obeys the above power law behavior (7,8,(11)(12)(13). However, in contrast to regular threedimensional structures, for proteins it is usually found that d s < 2 associating them to a realm of low dimensionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical value of ν = 1/d H serves as an order parameter of polymer phase structure: For a continuous self-nonintersecting chain in three space dimensions d H can in principle acquire any value between 1 and 3. Simple examples of fractal structures where d H is not an integer, include the piecewise linear Koch curve and attractors of chaotic equations such as the Lorenz and the Rössler equations [9].The phases of polymers and in particular proteins, have been presumed to display fractal geometry [10][11][12][13][14][15][16][17][18][19][20]. Traditionally, the following values of ν are assigned to these phases [1, 2]: Biologically active proteins are commonly in the space filling d H = 3 phase.…”
mentioning
confidence: 99%
“…The phases of polymers and in particular proteins, have been presumed to display fractal geometry [10][11][12][13][14][15][16][17][18][19][20]. Traditionally, the following values of ν are assigned to these phases [1, 2]: Biologically active proteins are commonly in the space filling d H = 3 phase.…”
mentioning
confidence: 99%